2012
DOI: 10.3389/fnbeh.2012.00025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced emotional reactivity after selective REM sleep deprivation in humans: an fMRI study

Abstract: Converging evidence from animal and human studies suggest that rapid eye movement (REM) sleep modulates emotional processing. The aim of the present study was to explore the effects of selective REM sleep deprivation (REM-D) on emotional responses to threatening visual stimuli and their brain correlates using functional magnetic resonance imaging (fMRI). Twenty healthy subjects were randomly assigned to two groups: selective REM-D, by awakening them at each REM sleep onset, or non-rapid eye movement sleep inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 59 publications
4
69
4
Order By: Relevance
“…Moreover, SD has detrimental effects on emotional memory encoding (Walker 2008) and consolidation reliant on hippocampus and mPFC (Sterpenich et al 2007). Emotional memory consolidation has been associated with REM sleep (Nishida et al 2009;Walker and van der Helm 2009), whereas REM SD is related to amplified activity in areas central to emotional processing, including the mPFC (Rosales-Lagarde et al 2012). The lack of SCR or fMRI effects in our study does not preclude that our experimental manipulation may have more long-term memory-encoding or consolidation effects.…”
Section: Effects Of Partial Sd On Associative Learning Processesmentioning
confidence: 64%
“…Moreover, SD has detrimental effects on emotional memory encoding (Walker 2008) and consolidation reliant on hippocampus and mPFC (Sterpenich et al 2007). Emotional memory consolidation has been associated with REM sleep (Nishida et al 2009;Walker and van der Helm 2009), whereas REM SD is related to amplified activity in areas central to emotional processing, including the mPFC (Rosales-Lagarde et al 2012). The lack of SCR or fMRI effects in our study does not preclude that our experimental manipulation may have more long-term memory-encoding or consolidation effects.…”
Section: Effects Of Partial Sd On Associative Learning Processesmentioning
confidence: 64%
“…Least-squares regression lines (thick lines) and 95% confidence interval bounds (thin lines) of the association between insomnia severity and the frequency of occurrence of short-lasting (gray) and long-lasting (black) distress after a shameful experience are shown. emotional experiences, both subjectively and objectively, at the level of limbic brain reactivity (10,(12)(13)(14). We hypothesized that this beneficial effect may be attenuated in conditions characterized by restless REM sleep (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…REM sleep plays an important role in this process (10,(12)(13)(14), although not excluding a role for nonrapid-eye-movement (NREM) sleep (15). Naps containing REM sleep were shown to resolve emotional reactivity, whereas naps without REM sleep did not (12).…”
mentioning
confidence: 99%
“…For example, Yoo, Gujar, Hu, Jolesz, and Walker (2007) found that sleep deprivation resulted in increased activation in the amygdala to negative emotional stimuli and dampened functional connectivity with the medial prefrontal cortex (Yoo et al, 2007). Thus, sleep deprivation both enhanced evoked NA associated with negatively valenced stimuli (see also Rosales-Lagarde et al, 2012) and impaired the capacity to downregulate this emotional response 3 .…”
Section: Sleep Disturbance and Namentioning
confidence: 95%